Comparison of high‐resolution and tandem mass spectrometry for the analysis of nerve agent metabolites in urine. (20th June 2013) - Hamelin, Elizabeth I.; Bragg, William; Shaner, Rebecca L.; Swaim, Leigh L.; Johnson, Rudolph C.
<x xml:space="preserve">Abstract</x> RATIONALE Although use is prohibited, concerns remain for human exposure to nerve agents during decommissioning, research, and warfare. High‐resolution mass spectrometry (HRMS) was compared to tandem mass spectrometry (MS/MS) analysis for the quantitation of five urinary metabolites specific to VX, Russian VX, soman, sarin and cyclosarin nerve agents. The HRMS method was further evaluated for qualitative screening of metabolites not included in the test panel. METHODS Nerve agent metabolites were extracted from urine using solid‐phase extraction, separated using hydrophilic interaction chromatography and analyzed using both tandem and high‐resolution mass spectrometry. MS/MS results were obtained using selected reaction monitoring with unit resolution; HRMS results were obtained using a mass extraction window of 10 ppm at a mass resolution of 50 000. The benchtop Orbitrap HRMS instrument was operated in full scan mode, to measure the presence of unexpected nerve agent metabolites. RESULTS The assessment of two quality control samples demonstrated high accuracy (99.5–104%) and high precision (2–9%) for both HRMS and MS/MS. Sensitivity, as described by the limit of detection, was overlapping for both detectors (0.2–0.7 ng/mL). Additionally, the HRMS method positively confirmed the presence of a nerve agent metabolite, not included in the test panel, using the accurate mass and relative retention time. CONCLUSIONS The precision, accuracy, and sensitivity were comparable between the current MS/MS method and this newly developed HRMS analysis for five nerve agent metabolites. HRMS showed additional capabilities beyond the current method by confirming the presence of a metabolite not included in the test panel. Published in 2013. This article is a U.S. Government work and is in the public domain in the USA.